PERANCANGAN JARINGAN FEMTOCELL PADA JARINGAN LTE MENGGUNAKAN MODEL PROPAGASI COST 231 MULTIWALL - Kevin Sean Farrel Manurung; Yuli Triyani (Politeknik Caltex Riau, 2021)
Caltex Riau Polytechnic Building has 3 floors which are always crowded with students, lecturers and staff every day. The network connection inside the building is not as good as the network connection outside the building because the signal from the BTS is attenuated by the thick walls of the building, causing the signal strength inside the building to be weak. The solution to overcome the problems that occur is to design an indoor Femtocell network on the LTE network in the building. Caltex Riau Polytechnic which can improve signal quality and expand coverage. This design applies the COST 231 Multiwall propagation model which will be simulated using RPS Software. Before designing the femtocell network, calculations are carried out based on Coverage and Capacity to get the required number of FAPs per floor. The simulation results get the average value of RSRP on each floor of the Main Building is -48.55 dBm, -48.81 dBm, -43.18 dBm and the average value of RSRP on each floor of the Multipurpose Building is -45.16 dBm, -51.16 dBm, -42.61 dBm. And the simulation results get the average SINR value on each floor of the Main Building is 20.96 dB, 21.86 dB, 24.46 dB and the average SINR value on each floor of the Multipurpose Building is 16.74 dB, 16.74 dB, 0 dB (because only 1 FAP is placed) The results obtained from the design have met the standard parameters used by the Tri operator.